Hubungan Pola Asuh Orang Tua dengan Kepercayaan Diri Kelas V SDN Gugus X Kota Bengkulu - Rahmawati, Hanifa; Dalifa (JURIDIKDAS, 2024)
This study aims to determine the relationship between parenting patterns and self-confidence of fifth grade students of SD Negeri Gugus X Bengkulu City. The type of research used is quantitative with correlation research method. The study population was all fifth grade students of SD Negeri Gugus X Bengkulu City, totaling 174 students. The sample of this study was elementary school students of Gugus X Bengkulu City which was taken by simple random sampling technique with a total of 44 students. The research instrument used was a questionnaire. Data collection techniques using a questionnaire. Data analysis techniques in this study using product moment correlation calculations. The results of this study indicate that the correlation coefficient is 0.427 with a significance level of 5% and n = 44, then rtabel is 0.297. So that the obtained rcount> rtable, namely 0.427> 0.297, with the contribution of variable X to variable Y amounting to 18.23%. It can be concluded that there is a relationship between parenting patterns and self-confidence of fifth grade students of SD Negeri Gugus X Bengkulu City with the level of correlation between variables in the moderate category. So that parents must be right in choosing parenting.